Analytical study of water safety parameters in ground water samples of Uttarakhand in India - Gaur S, Joshi M.C, Saxena S.K, Dutt H.K (Journal of Applied Pharmaceutical Science)
The main problem of the locality is the drinking water. Certain health problems are associated with people living in hills that are because of the presence of excess of heavy metals and other impurities. The present study was conducted to analyze the various parameters of ground water in uttarakhand, India and to check its fitness for drinking. It will also clarify the health hazards imposed on the population of this state. The present study was conducted in five regions of Uttarakhand, India (Haridwar, Vikasnagar, Mussoorie, Dehradun & Dakpathar). Ten samples of ground water were collected from each of the five regions during the pre-mansoon (Jan-Feb ) and post-mansoon (Sept-Oct )seasons.The pH was estimated by pH meter, acidity,alkalinity, sulphates,chorides,Total hardness(Ca & Mg) were determined by titration methods. The total suspended solid was calculated by the formula. The heavy metals like Mn, Al, Ba, Cd, Cr, Co, Cu, Fe and Pb were determined in the ground water samples by ICP mass spectroscopy. The concentrations of heavy metals, pH, alkalinity, sulphate, chloride, TDS & Total Hardness (TH) were compared with the standards by BIS for Drinking water (IS 10500:1991). The results shows that water pH of all the five regions showed no remarkable variation from the BIS recommended value of pH (6.5-8.5). The alkalinity was above the BIS desirable level of 200mg/l in all the samples, but was less than the maximum permissible limit. The Drinking water of all the regions contains higher amounts of TDS than the desirable limits. maximum TDS was detected in Haridwar & dehradun state. The ground water of mussoorie region shows total hardness to be above the BIS desirable level of 300mg/l. The chloride content was above the BIS desirable level of 250mg/l in dehradun only. The sulphate content was highest in haridwar (197.5mg/l) and dehradun (170mg/l) but it was below the desirable limit of 200mg/l. The Cd,Cr,&Pb content of all the five regions of Uttarakhand showed higher the BIS permissible limits of 0.01, 0.05 and 0.05 mg/l respectively. The content of Mn,Ba,Cu, Co&Fe are within the permissible limit of BIS standards for drinking water.
Keywords: Ground water, Hydro-chemical analysis, heavy metals, ICP mass spectroscopy.